(untitled) (Research, Society and Development, 2022)
Introduction: The present study aims to reflect on the care provided by health professionals with training in cardiology to patients with chronic heart failure (CHF) and their inclusion in palliative care (PC). Method: Descriptive study characterized as a narrative literature review. Pubmed, Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS), Web of Science and Health Science Descriptors (DECs) “chronic heart failure, phenomenology, humanization of care, spirituality, palliative care”. The text was organized under three aspects: clinical, humanistic and phenomenological. Results: The research resulted in 20 articles on the subject, its therapeutic approach and the behavior of health professionals towards CHF patients. Final considerations: A humanized care is necessary in the ICC and the approach of subjects such as spirituality and palliative care for these individuals.